EXAMINING THE EFFECTS OF EMPLOYEE HAPPINESS, LEADERSHIP AND AGILE MINDSET ON JOB PERFORMANCE - Sarwo Edie Setijono; Ervin Nora Susanti; Herni Widiyah Nasrul (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the effects of employee happiness, leadership, and agile mindset on job performance within organizational settings. In response to increasing demands for productivity and adaptability, organizations are placing greater emphasis on both human and behavioral factors that influence performance. This research adopts a qualitative approach to explore how these three variables individually and collectively shape employee outcomes. Data were collected through semi-structured interviews with selected participants and analyzed using thematic analysis to identify key patterns and relationships. The findings indicate that employee happiness significantly enhances motivation, engagement, and productivity, while effective leadership fosters a supportive environment that strengthens employee commitment and clarity of goals. Additionally, an agile mindset enables employees to adapt to change, collaborate effectively, and continuously improve their performance. Importantly, the study reveals that the interaction of these variables produces a synergistic effect, leading to higher levels of job performance than when each factor is considered independently. This study contributes to the existing literature by providing an integrated perspective on job performance and offers practical implications for organizations seeking to optimize workforce effectiveness. It highlights the need for holistic strategies that combine well-being, leadership development, and agility in modern workplaces.